With the Dead amidst Darkness: The Nekyomanteion of the Acheron - Chapinal-Heras, Diego (ARYS. Antigüedad: Religiones y Sociedades, 2023)
The aim of this study is to review the debate concerning the identification of the archaeological site of Mesopotamon, in the coast of Epirus, as the well-known Nekyomanteion of the Acheron. Throughout comparison and analysis of the arguments of each hypothesis, this paper will attempt to provide an accurate approach that allow us to discern the most solid theory.
Keywords: Nekyomanteion; Hades; Ephyra; Epirus; greek oracles; greek religion; necromancy; oracles of the death